2022
DOI: 10.1088/1748-9326/ac4f8e
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of atmospherically reactive gases nitrous acid and nitric oxide from Arctic permafrost peatlands

Abstract: Soils are important sources of nitric oxide (NO) and nitrous acid (HONO) in the atmosphere. These nitrogen (N)-containing gases play a crucial role in atmospheric chemistry and climate at different scales because of reactions modulated by NO and hydroxyl radicals (OH), which are formed via HONO photolysis. Northern permafrost soils have so far remained unexplored for HONO and NO emissions despite their high N stocks, capacity to emit nitrous oxide (N2O), and enhancing mineral N turnover due to warming and perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Bhattarai et al. (2022) reported considerable soil HONO emissions (0.1–2.4 μg N m −2 hr −1 ) from arctic permafrost peatlands, indicating that the arctic and subarctic soils may be significant sources of HONO. If we simply assumed continuously soil HONO emissions for 3 months in summer in the arctic permafrost peatlands, the calculated annual soil HONO emissions were in the range of 0.002–0.05 kg N ha −1 yr −1 , with a mean value of 0.019 kg N ha −1 yr −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhattarai et al. (2022) reported considerable soil HONO emissions (0.1–2.4 μg N m −2 hr −1 ) from arctic permafrost peatlands, indicating that the arctic and subarctic soils may be significant sources of HONO. If we simply assumed continuously soil HONO emissions for 3 months in summer in the arctic permafrost peatlands, the calculated annual soil HONO emissions were in the range of 0.002–0.05 kg N ha −1 yr −1 , with a mean value of 0.019 kg N ha −1 yr −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The average agricultural soil HONO flux was in the range of −0.86 to 20.25 ng N m −2 s −1 measured by field dynamic chambers (Tang et al, 2019), while our estimated value was ∼8.53 ± 1.61 ng N m −2 s −1 in the same location. Bhattarai et al (2022) reported considerable soil HONO emissions (0.1-2.4 μg N m −2 hr −1 ) from arctic permafrost peatlands, indicating that the arctic and subarctic soils may be significant sources of HONO. If we simply assumed continuously soil HONO emissions for 3 months in summer in the arctic permafrost peatlands, the calculated annual soil HONO emissions were in the range of 0.002-0.05 kg N ha −1 yr −1 , with a mean value of 0.019 kg N ha −1 yr −1 .…”
Section: Global and Regional Patterns Of Soil Hono Emissions Using An...mentioning
confidence: 99%
“…Methanogenesis in particular is responsible for fluxes of methane in warming tundra (131, 133, 134) and was associated with tundra in the current study. Additionally, a gene involved in nitric oxide cycling (PF08768) (135137), as well as a variety of anaerobic organisms and P-related genes (K03525, K00997, K00992, K13497, PF08009) (138140), also provide insight into the molecular functions of tundra in the context of global climate change. Interestingly, we also found evidence for pathogen resistance within the tundra genomic signature (PF11203, PF05045), lending credence to a small number of recent studies suggesting permafrost environments as one of the largest reservoirs of soil viruses (141144) and a possible linkage between soil methane and viral infection (145).…”
Section: Discussionmentioning
confidence: 99%
“…Methanogenesis in particular is responsible for fluxes of methane in warming tundra (131,133,134) and was associated with tundra in the current study. Additionally, a gene involved in nitric oxide cycling (PF08768) (135)(136)(137), as well as a variety of anaerobic organisms and P-related genes (K03525, K00997, K00992, K13497, PF08009) (138)(139)(140), also provide insight into the molecular functions of tundra in the context of global climate change.…”
Section: Soil Genomic Potential For Greenhouse Gas Emissions Differs ...mentioning
confidence: 99%
“…Gil et al [217] additionally found a positive correlation between N 2 O concentration and ammonium and CO 2 concentration and a negative one with nitrate concentration in the soil profile. Recently, bare peat sites on permafrost peatlands with high availability of inorganic N have also been identified as important sources of nitric oxide (NO, 1.42 ± 0.13 mg N m −2 d −1 ) and nitrous acid (HONO, 0.06 ± 0.02 mg N m −2 d −1 ) [255] (Table S1, Figure 4A). As with N 2 O, low emissions were detected from adjacent vegetated surfaces.…”
Section: Gaseous N Lossmentioning
confidence: 99%